The future of evapotranspiration: Global requirements for ecosystem functioning, carbon and climate feedbacks, agricultural management, and water resources. Issue 4 (10th April 2017) - Fisher, Joshua B.; Melton, Forrest; Middleton, Elizabeth; Hain, Christopher; Anderson, Martha; Allen, Richard; McCabe, Matthew F.; Hook, Simon; Baldocchi, Dennis; Townsend, Philip A.; Kilic, Ayse; Tu, Kevin; et al.
Abstract: The fate of the terrestrial biosphere is highly uncertain given recent and projected changes in climate. This is especially acute for impacts associated with changes in drought frequency and intensity on the distribution and timing of water availability. The development of effective adaptation strategies for these emerging threats to food and water security are compromised by limitations in our understanding of how natural and managed ecosystems are responding to changing hydrological and climatological regimes. This information gap is exacerbated by insufficient monitoring capabilities from local to global scales. Here, we describe how evapotranspiration (ET) represents the key variable in linking ecosystem functioning, carbon and climate feedbacks, agricultural management, and water resources, and highlight both the outstanding science and applications questions and the actions, especially from a space‐based perspective, necessary to advance them. Key Points: ET science and applications have significantly advanced across a wide array of fields over the past several decades Critical outstanding ET‐based research and applied science questions from local to global scales remain due to deficiencies in our observational capabilities National and international research priorities should include ET‐focused satellite observational investments and programs